2020
DOI: 10.1039/c9ee02028d
|View full text |Cite
|
Sign up to set email alerts
|

Band-bending induced passivation: high performance and stable perovskite solar cells using a perhydropoly(silazane) precursor

Abstract: It could successfully control the band-bending of the perovskite semiconductor, which led to improvement of the photovoltaic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
121
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 53 publications
8
121
0
Order By: Relevance
“…Recently, several publications have reported empirically developed strategies to improve device performance, by employing such passivation layers at the perovskite/HEL interface. [ 34–38 ] However, the exact mechanism behind these passivation strategies is still not investigated in detail. The findings reported in this study may give a first understanding about the role of passivation layers at the perovskite/HEL interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several publications have reported empirically developed strategies to improve device performance, by employing such passivation layers at the perovskite/HEL interface. [ 34–38 ] However, the exact mechanism behind these passivation strategies is still not investigated in detail. The findings reported in this study may give a first understanding about the role of passivation layers at the perovskite/HEL interface.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of the n‐MAPI/p‐HEL interface might also explain, why many of the recently reported passivation layers that are used to improve the PCE are employed in between the perovskite absorber and the HEL. [ 34–38 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–12 ] In order to further improve the stability and efficiency of PSCs, it is necessary to select appropriate passivators to modify the interface of the PVSK layer. [ 13–16 ] In the past few years, numerous studies have demonstrated that functional groups, such as pyridine, thiophene, iodopentafluorobenzene, [ 17 ] cyano, [ 18 ] sulfonate (OSO 3 − ), [ 19 ] fluorine, carboxylic acid could act as the passivator of defects in perovskite film, for example, under‐coordinated Pb 2+ cations, and hence reduce the nonradiative charge recombination. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] In fact, numerous PSCs throughout the literature demonstrate severely hampered stability under illumination. [31,32] Therefore, the photostability is essential for the commercial success of single-junction PSCs and tandem solar cells that combines perovskites with silicon.…”
Section: Introductionmentioning
confidence: 99%